Investigations in teaching and learning languages : studies in honour of hanna komorowska - Piechurska-Kuciel, Ewa; Zybert, Jerzy; Gabrys-Barker, Danuta (Second Language Learning and Teaching, 2013)
The book presents most recent investigations into foreign language teaching and learning discussed by prominent scholars in the field. A wide variety of topics ranges from theoretical approaches to foreign language instruction to a discussion of findings of empirical research in language learning and pedagogy. The theoretical part of the volume tackles issues which constitute the backbone to the understanding of the processes involved in language development, learning and teaching and thus contribute to applied research. The empirical articles in Parts Two and Three of the volume report on studies focusing on such important issues as various dimensions of awareness (language, cross-cultural competence or affectivity) and specific methodologies implemented in different educational settings (such as, for instance, dyslexic learners) or in teacher training programmes.